A combined experimental and theoretical approach to study SmC → NcybC phase transition in a four-ring bent-core liquid crystal. (14th June 2016) - Singh, Swapnil; Deb, Rahul; Chakraborty, Nirmalangshu; Singh, Harshita; Gupta, Vineet; Sinha, Kirti; Tandon, Poonam; Omelchenko, Myroslava; Rao, Nandiraju Venkata Satyanarayana; Ayala, Alejandro Pedro
Abstract : Spectroscopic evidences for the analysis of phase transition and hydrogen bonding in a newly synthesised four-ring bent-core liquid crystal. Abstract : A newly synthesized four-ring bent-core liquid crystal (BCLC) has been studied using experimental and quantum chemical approach. Differential scanning calorimetry (DSC), polarised optical microscopy (POM), and X-ray investigations were carried out to identify the phase transitions and associated phases. DSC along with POM revealed four phase transitions i.e. Cr → SmX → SmC → NcybC → Iso in the temperature range from 30 °C to 180 °C. The existence of smectic C like fluctuations also known as cybotactic groups in the broad temperature range of the nematic phase was confirmed by small angle X-ray diffraction. Conformational and vibrational analyses have been performed using density functional theory (DFT), to identify the most stable conformer having a bent shape. Analysis of the potential energy surface (PES) for different torsional angles revealed the most probable conformational states for the BCLC. Temperature dependent Fourier transform infrared (TD-FTIR) spectroscopy is used to study phase transitions and revealed marked changes in the spectral line shape especially the vibrations of OH, CH2, CH3, CO, and HCN groups during the SmC → NcybC phase transition above ∼95 °C. A good agreement between the calculated and observed infrared spectra validates the structure of this conformer that has been used for further studies.